2013
DOI: 10.1002/term.1756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of platelet-rich plasma (PRP) concentration on proliferation, neurotrophic function and migration of Schwann cellsin vitro

Abstract: Platelet-rich plasma (PRP) contains various growth factors and appears to have the potential to promote peripheral nerve regeneration, but evidence is lacking regarding its biological effect on Schwann cells (SCs). The present study was designed to investigate the effect of PRP concentration on SCs in order to determine the plausibility of using this plasma-derived therapy for peripheral nerve injury. PRP was obtained from rats by double-step centrifugation and was characterized by determining platelet numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 43 publications
2
80
1
3
Order By: Relevance
“…It is an autologous preparation utilizing the patient’s own blood. Increasing evidence has highlighted the positive effects of PRP on peripheral nerve regeneration with acceptable safety profiles in experimental studies 916 . Farrag et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is an autologous preparation utilizing the patient’s own blood. Increasing evidence has highlighted the positive effects of PRP on peripheral nerve regeneration with acceptable safety profiles in experimental studies 916 . Farrag et al .…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al . 16 showed that PRP could stimulate Schwann cell proliferation, secretion of nerve growth factor, and neurotrophic factor in vitro . In contrast, Piskin et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…67, 68, 72, 84, 85, 86 In rat studies, the average whole-blood platelet count has been reported to be 478.12 × 10 3  μL −1 , and the average platelet count of PRP was 3 221.34 × 10 3  μL −1 , 72 whereas the effective concentration of platelets in another investigation using rats was 1 500 × 10 3 platelets per μL. 67 Similarly, in an ovine model, restoration of motor function at 12 weeks after peroneal nerve compression injury was achieved using scaffolds and PRGF injections; the platelet count was 202 × 10 3 –349 × 10 3  μL −1 .…”
Section: Prp Treatment: Preparation and Biological Characteristicsmentioning
confidence: 99%